2004
DOI: 10.1074/jbc.m309663200
|View full text |Cite
|
Sign up to set email alerts
|

Native and Inhibited Structure of a Mu class-related Glutathione S-transferase from Plasmodium falciparum

Abstract: The parasite Plasmodium falciparum causes malaria tropica, the most prevailing parasitic disease worldwide, with 300 -500 million infections and 1.5-2.7 million deaths/year. The emergence of strains resistant to drugs used for prophylaxis and treatment and no vaccine available makes the structural analysis of potential drug targets essential. For that reason, we analyzed the three-dimensional structure of the glutathione S-transferase from P. falciparum (Pf-GST1) in the apoform and in complex with its inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…The basic procedure utilized the purified expression vector pJC20 containing the complete cDNA of the PfGST as an insert (18) and two synthetic oligonucleotide primers designed to introduce the proper mutations. In mutant A, the flexibility of the loop region was lowered by the substitution of Thr-113 and Asn-119 by two prolines.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The basic procedure utilized the purified expression vector pJC20 containing the complete cDNA of the PfGST as an insert (18) and two synthetic oligonucleotide primers designed to introduce the proper mutations. In mutant A, the flexibility of the loop region was lowered by the substitution of Thr-113 and Asn-119 by two prolines.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in these mutants the inactivation process becomes at least 100 times slower than in the native enzyme. Recent studies based on gel filtration experiments have demonstrated that the inactivation caused by the absence of GSH is coupled to a tetramerization process (16,18). This Tetramerization and Cooperativity in P. falciparum GST AUGUST 14, 2009 • VOLUME 284 • NUMBER 33…”
Section: Kinetic Properties Of Loop 113-119 Mutants-selected Mutationmentioning
confidence: 99%
See 2 more Smart Citations
“…A gene encoding a protein with sequence identity of up to 33% with known GSTs was identified on chromosome 14 of P. falciparum. The three-dimensional structure of PfGST shares several structural features with the Mu class GSTs even though alignments with its members display low sequence identities (20 -33%) (12). Despite this structural similarity with Mu class GSTs, PfGST shows very low or no affinity toward the classical GST substrates.…”
mentioning
confidence: 99%